Jenama dan Citra: Strategi Aktivasi Merek Kabupaten Ponorogo Melalui “Fantastic Ponorogo” - Mela Siti Maisaroh; Rhesa Zuhriya Briyan Pratiwi (Lisyabab : Jurnal Studi Islam dan Sosial, 2021)
Each region has characteristics in a number of tourist destinations that it manages. In this case, Ponorogo Regency is famous for several tourist objects, those referring to natural tourism, cultural tourism, religious tourism, to tourism in a special concept. Since 2019, Ponorogo Regency has carried out its tourism branding through a special brand "Fantastic Ponorogo". This study aims to describe the branding process of Ponorogo Regency in order to improve the brand image as Fantastic Ponorogo, in terms of brand activation. This research uses a qualitative descriptive strategy, with data collection through observation, interviews, and documentation. The results showed that the use of advertising through several media was deemed effective and rife to improve the image of Ponorogo as a fantastic tourist city. Brand activation is also supported by brand activation through marketing events which are massively published through a number of online media platforms.